Strategic Feasibility Analysis for Business Expansion in a Textile Company - Regina Suhadi; Yuliani Dwi Lestari (Green Publisher Indonesia, 2026)
This research examines the strategic, operational, and financial viability of CV Surya Abadi Putra Kembar's (SAPK) expansion into the beauty cotton business. Market analysis reveals significant growth potential driven by increasing hygiene awareness, home-based beauty practices, and e-commerce development in Indonesia. STP analysis identifies urban and suburban young women with high purchasing power as the primary target market, favoring locally manufactured, high-quality, and environmentally friendly products. Operational analysis evaluates three models: full in-house, hybrid (Partial Maklon), and full outsourcing, with the hybrid model offering the optimal balance of cost-effectiveness, scalability, and quality control. A 10-year financial forecast demonstrates positive NPV, IRR exceeding the company's benchmark, and short payback period across all scenarios. Monte Carlo simulation confirms high probability of sustained positive cash flow. The Partial Maklon model emerges as the most feasible strategy, combining SAPK's operational strengths with external partners' efficiency while minimizing capital investment and risk. This model projects an NPV of approximately IDR 180 billion, IRR above 12%, three-year payback period, and only 5% loss probability. The study confirms SAPK's operational capability to transform from raw material supplier to branded consumer goods producer, enhancing long-term competitiveness and supporting Indonesia's industrial value chain development.